2018
DOI: 10.1093/conphys/coy050
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ocean Acidification and Warming on the bioenergetics of developing eggs of Atlantic herring Clupea harengus

Abstract: Ocean Acidification and Warming induce trade-offs in development and growth of Atlantic herring embryos by altering mitochondrial function and increasing the animal’s energy demand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
21
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 56 publications
6
21
2
Order By: Relevance
“…Similar results were reported in a study where high temperature decreased the hatching success of Clupea harengus 32 . Clutches produced under higher temperature had fewer and smaller eggs, and these couples had overall a smaller reproductive output.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar results were reported in a study where high temperature decreased the hatching success of Clupea harengus 32 . Clutches produced under higher temperature had fewer and smaller eggs, and these couples had overall a smaller reproductive output.…”
Section: Discussionsupporting
confidence: 90%
“…Metabolic demands increase with temperature 32 . This could explain the lower investment in reproductive output at high temperature observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Leo et al (2018) suggest that the differing responses to high pCO 2 observed in Atlantic herring, a congener species to Pacific herring, may be explained by environmental acclimation. High pCO 2 is regularly observed in the Kiel Fjord, and little to no effect of highly elevated pCO 2 was observed in Atlantic herring larvae from this location (Franke and Clemmesen, 2011), compared to significant effects in larvae from populations spawning in relatively low pCO 2 in the Oslo Fjord (Frommel et al, 2011;Leo et al, 2018). Diel and tidal cycles in coastal environments may also contribute to a lack of embryo sensitivity to elevated pCO 2 (Cross et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, despite the fact that studies on the energetic results of human disturbance in bioindicator species are limited to a few examples (Adams & Ham, 2011;Toro, Navarro, & Palma-Fleming, 2003), there are several examples to show that alterations in the physiological/energetic conditions of nonbioindicator organisms are due to direct (Williams, Lusseau, & Hammond, 2006;Symons, Pirotta, & Lusseau, 2014;Villegas-Amtmann, Schwarz, Sumich, & Costa, 2015) and indirect human impacts (Griffen, 2018;Leo, Dahlke, Storch, Pörtner, & Mark, 2018;Thomas et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Species may also alter their feeding habits (Griffiths et al, ; Jokimäki, Suhonen, Jokimäki‐Kaisanlahti, & Carbó‐Ramírez, ) and trophic interactions (Costa, Tavares, Suciu, Rangel, & Zalmon, ; Gray, Baldauf, Mayhew, & Hill, ) in areas with human disturbance, and thus these changes in behavior and daily activities can result in changes to the energy balance and physiological state (Chandurvelan, Marsden, Glover, & Gaw, ; Spellerberg, ). Therefore, despite the fact that studies on the energetic results of human disturbance in bioindicator species are limited to a few examples (Adams & Ham, ; Toro, Navarro, & Palma‐Fleming, ), there are several examples to show that alterations in the physiological/energetic conditions of nonbioindicator organisms are due to direct (Williams, Lusseau, & Hammond, ; Symons, Pirotta, & Lusseau, ; Villegas‐Amtmann, Schwarz, Sumich, & Costa, ) and indirect human impacts (Griffen, ; Leo, Dahlke, Storch, Pörtner, & Mark, ; Thomas et al, ).…”
Section: Introductionmentioning
confidence: 99%